Assessing the quality of generalized variance functions - Inken Siems; Ralf Münnich (AStA Wirtschafts- und Sozialstatistisches Archiv, 2026)
Generalized variance functions (GVFs) are widely used in official statistics to approximate sampling variances when direct variance estimation is impractical. However, their reliability is highly context-dependent. This study evaluates GVF performance through guided modeling strategies and simulation studies across diverse sampling designs and data settings. Results show that GVFs perform well under ideal conditions, but their accuracy deteriorates in the presence of mixture distributions, rare domains, unstable variances or poor groupings. We provide practical recommendations on grouping variables, selecting training samples, and applying diagnostic checks, emphasizing predictive validity over model fit. Our findings underscore the importance of careful quality assessment for GVFs and the need for application-specific validation prior to use. – – Verallgemeine Varianzfunktionale (GVFs) werden in der amtlichen Statistik häufig eingesetzt, um Stichprobenvarianzen zu approximieren, wenn eine direkte Varianzschätzung nicht praktikabel ist. Ihre Zuverlässigkeit erweist sich jedoch als stark kontextabhängig. Diese Studie bewertet die Qualität von GVFs anhand von Simulationsstudien unter verschiedenen Stichprobendesigns und Datensituationen. Die Ergebnisse zeigen, dass GVFs unter idealen Bedingungen verlässliche Annäherungen liefern, ihre Genauigkeit jedoch bei Mischverteilungen, seltenen Domänen, instabilen Varianzen oder ungeeigneten Gruppierungen deutlich abnimmt. Wir geben praxisorientierte Empfehlungen zur Gruppierung, Konstruktion und Diagnostik von GVFs. Dabei ist die prognostische Validität gegenüber bloßer Modellanpassung vorzuziehen. Unsere Ergebnisse verdeutlichen die Bedeutung einer sorgfältigen Qualitätsbewertung von GVFs sowie die Notwendigkeit einer anwendungsspezifischen Validierung vor ihrem Einsatz.
Keywords: 510; Survey sampling; Variance estimation; Generalized Variance Functions; Official statistics; Stichprobenverfahren; Varianzschätzung; Allgemeine Varianzfunktionale; Amtliche Statistik